Ceftolozane-Tazobactam Resistance in Multidrug-Resistant Pseudomonas aeruginosa Isolates Not Associated with AmpC Activity. (4th October 2017) - Tran, Truc T; Diaz, Lorena; Abodakpi, Henrietta; Ardila, Javier; Cadena, Elsa De La; Rios, Rafael; Miller, William; Rivas, Lina; Dinh, An; Porras, Paola; Panesso, Diana; Tam, Vincent; et al.
Abstract: Background: Ceftolozane-tazobactam (CT) is a newly approved cephalosporin/β-lactamase inhibitor combination with excellent in vitro activity against multidrug-resistant (MDR) P. aeruginosa . Unfortunately, CT-resistance (CT-R) has already been reported. In this work, we evaluate mutational pathways associated with high level of CT-R and assess the role of AmpC in a clinical strain-pair of MDR P. aeruginosa . Methods: A CT susceptible isolate of P. aeruginosa (2365) and its CT-R derivatives (2366 and 2367) were recovered from the infected device of a patient before and after treatment with CT. Minimum inhibitory concentrations (MICs) to CT were determined by Etest. Resistance mediated by AmpC hyperproduction was evaluated using ceftazidime (CAZ) and meropenem (MER) with and without cloxacillin (CLOX) at concentration of 1 mg/ml. In addition, the β-lactamase hydrolysis activity was determined for crude cell lysate of the isolates using a spectrophotometric assay for nitrocefin degradation. Furthermore, whole genome sequencing of the three strains was performed and compared (2365 vs. 2366 and 2367). Reads from each isolate were mapped against the genome of the reference strain PAO1. Variants identified by GATK, SamTools and CLC Genomics Workbench 8.5 were selected and annotated with SnpEff. Results: Strain 2365 had a CT MIC of 0.75 mg/ml while 2366 and 2367 have MICs > 256 mg/ml. AmpC hyperproduction test was positive only for the susceptible isolate (2365). In concordance, the hydrolysis assay showed a lack of nitrocefin degradation by CT-R 2366 compared with its CT-susceptible isolate 2365. Notably, the three strains (S and R) exhibited a truncated AmpD. Comparison of the resistant derivatives vs. 2365 and 2367 showed a 7 amino acid deletion in the Ω-loop of the β-lactamase AmpC in both resistant derivatives and mutations in genes predicted to encode a hypothetical protein, an ABC transporter ATP-binding protein and a multidrug resistance operon repressor MexR. Conclusion: Our results suggest that the deletion in the Ω-loop of AmpC in 2366 and 2367 does not contribute to CT-R in these P. aeruginosa strains. Further characterization of AmpC and other predicted proteins identified by WGS are needed to determine the mechanism of CT-R. Disclosures: All authors: No reported disclosures.